KEJAHATAN ALIENATIF - H e r m a n s y a h H e r m a n s y a h (Jurnal Dinamika Hukum, 2008)
The exictency of state of law in social life is certainly and its clear that impact of all our live, these conditions, of course, are able to impact on our life, likely, ideology, economy, cultural and social life. Moreover, are eliminated of lacal law that there are along ago. And then, sometime, appeared resistance from community where the local law become their way of life. This condition, are able to say that “eliminated crime” are accoured. Kata kunci: state of law, local law and eliminated crime.